New Antarctic gravity anomaly grid for enhanced geodetic and geophysical studies in Antarctica. Issue 2 (21st January 2016) - Scheinert, M.; Ferraccioli, F.; Schwabe, J.; Bell, R.; Studinger, M.; Damaske, D.; Jokat, W.; Aleshkova, N.; Jordan, T.; Leitchenkov, G.; Blankenship, D. D.; Damiani, T. M.; et al.
Abstract: Gravity surveying is challenging in Antarctica because of its hostile environment and inaccessibility. Nevertheless, many ground‐based, airborne, and shipborne gravity campaigns have been completed by the geophysical and geodetic communities since the 1980s. We present the first modern Antarctic‐wide gravity data compilation derived from 13 million data points covering an area of 10 million km 2, which corresponds to 73% coverage of the continent. The remove‐compute‐restore technique was applied for gridding, which facilitated leveling of the different gravity data sets with respect to an Earth gravity model derived from satellite data alone. The resulting free‐air and Bouguer gravity anomaly grids of 10 km resolution are publicly available. These grids will enable new high‐resolution combined Earth gravity models to be derived and represent a major step forward toward solving the geodetic polar data gap problem. They provide a new tool to investigate continental‐scale lithospheric structure and geological evolution of Antarctica. Key Points: New 10 km grid of terrestrial gravity anomalies in Antarctica, covering 73% of the continent Enabling determination of new high‐resolution combined Earth gravity models Providing new tool to investigate lithospheric structure and geological evolution of Antarctica